Evidence into Practice. Issue 1 (January 2015) - Boutis, Kathy; Howard, Andrew; Constantine, Erika; Cuomo, Anna; Somji, Zeeshanefatema; Narayanan, Unni G.
<x xml:space="preserve">Abstract</x> Objectives: Removable splints when compared with circumferential casts in randomized trials have been shown to be a safe and cost-effective method of managing many common minor distal radius and fibular fractures. This study estimated the extent to which this evidence is being implemented in clinical practice, and determined the perceived barriers to the adoption of this evidence. Methods: A cross-sectional survey of practicing orthopaedic surgeon members of the Pediatric Orthopedic Surgeons of North America (POSNA) was conducted, using a 22-item online questionnaire, and distributed using a modified Dillman technique. Survey questions were derived from and validated by literature review, expert opinion, and pilot-testing on the targeted sample before implementation. Results: Of the 826 eligible participants, 558 (67.6%) responded to the survey. Of these, 505 (90.5%) had completed a fellowship in pediatric orthopaedics, 335 (60.0%) worked in a university-affiliated setting, and 377 (67.6%) had been in practice for <20 years. Only 158/543 [29.1%; 95% confidence interval (CI), 25.28, 32.92] reported using a removable splint to treat buckle fractures of the distal radius; 32 (5.9%; 95% CI, 3.9, 7.9) and 8 (1.5%; 95% CI, 0.5, 2.5) would use such splints for minimally displaced greenstick and transverse fractures of the distal radius, respectively. For distal fibular avulsion fractures, 122 (22.5%; 95% CI, 19.0, 26.0) would use a removable splint; 57 (10.5%; 95% CI, 7.9, 13.1) and 28 (5.6%; 95% CI, 3.7, 7.5) would do so for nondisplaced Salter-Harris I and II fractures of the distal fibula, respectively. The most commonly reported perceived barriers to application of a removable device were concerns about patient compliance, potential complications, and possible medicolegal implications. Conclusions: Only a relatively small proportion of practicing POSNA use such splints for minor distal radius and distal fibular fractures. These data support the need for implementation of knowledge translation strategies (eg, education) targeted at all the stakeholders to encourage pediatric orthopaedic surgeons to change practice in keeping with the best evidence for these common and stable injuries. Level of Evidence: Level II.